Pest control treatment : a case study at administration office building for Majlis Perbandaran Manjung / Nur Anisah Muhammad Othman - Muhammad Othman, Nur Anisah (Universiti Teknologi Mara, Perak, 2014)
Majlis Perbandaran Manjung (MPM), they have 2 sections of building. Section one is known as old administration building aged around 19 years old and for the other section known as new administration building aged around 12 years old. Old administration building has 2 floors while the other has 3 floors. The old administration building contains several departments such as Building Department, Department of Information Technology and Department of Management Services. And for the next door building, there are Engineering and Maintenance Department and Department of Law and so on.